PERAN ORANG TUA DAN SOSIAL MEDIA TERHADAP PERILAKU SEKSUAL PRANIKAH PADA REMAJA KARANG TARUNA DI DESA CAMPURDARAT: APAKAH BERHUBUNGAN? - Ayu Dewi Ernawati; Dzinun Hadi (Al-Isyraq: Jurnal Bimbingan, Penyuluhan, dan Konseling Islam, 2022)
This study aims to determine the relationship between the role of parents and social media on premarital sexual behavior in youth youth organizations in Campurdarat Village. In this study, researchers used a quantitative approach with a correlation design. The population in this study amounted to 40 youth youths and the sample was determined through saturated sampling technique so that the large number of samples was 40 youth youths. The results showed that there was a relationship between the role of parents and social media on premarital sexual behavior in youth youth organizations in Campurdarat Village.